Effect of dietary octacosanol concentration extracted from triticale sprout on laying performance, egg quality, and blood parameters of laying hens - Chun Ik Lim; Kyeong Seon Ryu (Journal of Animal Science and Technology, 2022)
This study was conducted to investigate the effect of dietary supplementation of octacosanol (OCT) extracted from triticale sprout on laying performance, egg quality, and blood parameters of laying hens. A total of 192, Hyline brown laying hens aged 43 weeks were divided into 4 dietary groups of 48 birds each and they were randomly subjected to one of the experimental diets containing OCT at the levels of none, 10, 20, and 30 mg/kg of diet. All birds were fed with isoenergetic and isonitrogenous mash diets for 6 weeks. The result showed that hens supplemented with 20 and 30 mg/kg OCT in diet significantly increased (p < 0.05) egg production than those fed with the basal diet. OCT concentration in the egg yolk of hens fed with 20 and 30 mg/kg OCT was significantly higher than in those fed the control diet. Hens fed 20 and 30 mg/kg OCT exhibited greater high-density lipoprotein (HDL) cholesterol and interleukin (IL) concentrations and reduced serum concentrations of cholesterol and triglyceride compared to those fed with 0 and 10 mg/kg OCT. This study indicates that supplementing the diet of laying hens with 20 and 30 mg/kg of OCT can improve the performance, egg quality, and health status of laying hens.